Peptídeo natriurético tipo C no líquido folicular humano: relação com a maturação oocitária - Maíra Casalechi Badin Telles (2019)
C-type natriuretic peptide (CNP) is a product of granulosa cells (GC) that binds to a transmembrane receptor (natriuretic peptide receptor type 2, NPR2) and signals through the second messenger cyclic guanosine monophosphate (cGMP). Studies in mice have shown that CNP signaling contributes to ovarian follicle growth and oocyte meiotic arrest until the preovulatory luteinizing hormone (LH) surge. In humans, however, the relationship between follicular CNP levels and oocyte meiotic resumption is still unknown. The aim of this study was to investigate whether ovarian CNP levels and NPR2 expression change according to the meiotic phase of human oocytes. We collected follicular fluid (FF) and mural GC in pool from several follicles (n=47 participants), and FF, mural GC and CC from 96 preovulatory follicles (n=39 participants) of women undergoing controlled ovarian stimulation (COS) for in vitro fertilization (IVFI). We kept track of the maturation stage of each oocyte from follicles assessed individually at the time of oocyte denudation. CNP levels were measured in the FF by enzyme immunoassay. The mRNAs encoding for the CNP precursor NPPC and its receptor NPR2 were quantified by reverse-transcription real-time PCR (RTPCR). There was a positive linear correlation between CNP levels in FF pools and basal antral follicle counting (rs=0,458; p=0,002), number of preovulatory follicles >16 mm (rs=0,361; p=0,016) and number of oocytes retrieved (rs=0,378; p=0,011) and a negative correlation between CNP levels in FF pools and the percentage of mature (metaphase II, MII) oocytes retrieved (rs=-0,39; p=0,033). FF CNP levels in follicles containing MII oocytes were considerably lower than in follicles containing immature (metaphase I, MI) oocytes (median = 0.44 vs. 0.57 ng/ml, p < 0.05). Accordingly, NPPC gene expression was reduced by 50% in the GC from follicles containing MII oocytes when compared to GC from follicles containing MI oocytes (p<0.01). In addition, NPR2 mRNA was downregulated in CC surrounding MII oocytes compared to CC from MI oocytes (60% reduction, p<0.01). LH receptor mRNA expression was detected in both CC and GC of follicles containing MII or MI oocytes, being four-fold more abundant in CC than in GC. CNP signaling is downregulated in human ovarian follicles containing mature oocytes. Further in vitro studies should clarify whether CNP signaling is essential to keep oocyte meiotic arrest in humans.